Effects of planting interval and soil type on volume production and slenderness index of poplar (Populus nigra L.) plantations in Diwandareh region (Kurdistan province, western Iran) - Reyhane LATIFY; Ahmad ALIJANPOUR; Abas Banj SHAFIEI; Arezou SADEGHI (Journal of Forest Science, 2018)
Tests were done on seven poplar (Populus nigra Linnaeus) plantations to investigate the effects of planting interval of stands and soil properties on total volume production, commercial volume production and slenderness index. The parameters of stands like diameter at breast height, total height, stem height, total volume, commercial volume and slenderness index were measured and compared with soil characteristics and planting intervals. Results showed significant differences in qualitative characteristics of poplar stands in relation to tested planting intervals and physical soil characteristics. The highest mean commercial volume was found at planting interval of 2 × 2 m and at slenderness index mean near one. Characteristics of poplar stands showed the strongest correlation with physical properties of soil rather than with chemical ones. Soil properties had a higher effect on quantitative characteristics of the studied poplar stands in comparison with planting interval.